Propriedades estocásticas em variedades riemannianas - Oliveira, Jobson de Queiroz (2012)
In this thesis we studied two objects(?): properties in Riemannian manifolds, more precisely stochastic completeness, parabolicity and the Feller property and geometric properties of Bakry Emery Ricci tensor. First, we studied such stochastic properties on Riemannian and isometric immersions. The initial motivation was the work of Pigola and Setti [30] about the Feller property. In our first result, we proved that if a isometric immersion on a Cartan-Hadamard manifold has bounded mean curvature vector then the immersion is Feller. An analogous result was know for stochastic completeness. After we stabilish necessary and sufficient conditions to a Riemannian submersion be stochastically complete (parabolic). More precisely if a Riemannian submersion has minimal fiber and the total space is stochastically complete (parabolic ) then the basis is also stochastically complete ( parabolic ). Conversely, if the Riemannian submersion has compact minimal fiber and the basis is stochastically complete ( parabolic, Feller ) then the total space also is. We also proved that if a Riemannian submersion has compact minimal fiber then the total space is Feller if, and only if the the basis is Feller. In the second part we studied the Barkry Emery Ricci tensor Ricf, wich is a natural extension of the Ricci tensor in the context of weighted manifolds. We studied the following: suppose that Ricf has a lower bound –cG where G is a smooth nonnegative function and c a positive constant. Such lower bound allow us to obtain some geometric and topological consequences as we describe below. Consider Mf a weighted Riemannian manifold. The first consequence is an upper estimate, outside a geodesic ball of radius r0, for the weighted Laplacian of the Riemannian distance in terms of the function G. Let Mf be a weighted Riemannian manifold and po Є Mf fixed. Our first result is an upper bound, outside of a geodesic ball of radius R centered in po, for the weighted Laplacian os the Riemannian distance function from po in terms od the function G. The first consequence of this estimate is an estimate for the weighted volume Volf (B(R)) of a geodesic ball with radius R in terms of the integral of G. This estimate together the assumption of f be radial and Ә f ≥ - a, a≥ 0 (or | f | ≤k ) allow us to prove a comparison theorem for mf e mag, the Laplacian of distance function of the Riemannian model fo curvature aG, as such as a comparison theoremfor the weighted volume of a geodesic ball with radius R on the Riemannian model MaG, with curvature aG. Using a weighted version of the Bochner formula we proved that Ricf ≥ G’ then Mf satisfies the Omori-Yau Maximum Principle, where G is a positive, nondecreasing smooth function, such that G-1 does not belong to L1(Mf). In particular we conclude that Mf is stochastically complete. The next result we proved extends, for the tensor Ricf, a type Myers theorem due to Ambrose [1]. For this an additional assumption on f was required. As an aplication of this result we extended a result about compacity of Ricci solitons due to Fernandez-Lopez e García-Rio [15]. In 1976, Yau [36] proved an estimate for the gradient of a positive harmonic funcion u, defined on B(2R), when M is complete and Ric ≥ -k, k≥ 0. Such estimate depends only on R and k and was extended, to the weighted, to the case, to f-harmonic positive functions, when Ricf ≥ - k and Ric ≥ - H, k, H ≥ 0. Brighton [9] obtained estimates for the gradient of a positive f-harmonic function assuming only Ricf ≥ -k. We obtained estimates for the case Ricf ≥ -G where G is a smooth nonnegative function and when f= G = 0 we recover the original estimate of Yau. Finally we proved a comparison theorem between the first eigenvalue of the geodesic ball of radius r on Mf and the first eigenvalue of the geodesic ball of radius r of the model MG. Such result extends, to the weighted case, a result due to Bessa e Montenegro [4].